Comparison of the effect of guava leaf extract (Psidium guajava L.) with polyvinylpyrrolidone-sodium hyaluronate on the number fibroblasts (study on white rats [Rattus norvegicus]) - Hakim, Rachmi Fanani; Fakhrurrazi, Fakhrurrazi; Zamzami, Fatimah Sahara (Odonto : Dental Journal, 2023)
Background: Wound healing is a cellular and complex process that aims to restore the integrity of tissue damaged by injury. The phases that occur in the wound healing process are inflammation, proliferation, and maturation (remodeling). One of the final results of wound healing is fibroblasts proliferation. Fibroblasts have the ability to synthesize collagen fibeBackground: Wound healing is a cellular and complex process that aims to restore the integrity of tissue damaged by injury. The phases that occur in the wound healing process are inflammation, proliferation, and maturation (remodeling). One of the final results of wound healing is fibroblasts proliferation. Fibroblasts have the ability to synthesize collagen fibers that will cover the injured area. Natural medicinal plants that have the potential to accelerate wound healing are guava (Psidium guajava L.) leaves which contain flavonoids, tannins, saponins, and alkaloids. Polyvinylpyrrolidone-sodium hyaluronate gel is one of the wound treatment products on the market and can help the wound healing process Methods: This research method was an experimental laboratory using 10 white rat samples which were divided into two groups and given injury to the mandibular anterior gingiva. Both treatment groups were applied topically in the morning and evening for 14 days, then the tissue was observed histologically. Results: Observation of the number of fibroblasts in the treatment group applied to guava leaf extract gel had a mean of 28Â±11 while the treatment group applied Polyvinylpyrrolidone-sodium hyaluronate gel was 10Â±4. The unpaired t test (Independent T-Test) showed a significance value of 0.000 (p